2011
DOI: 10.1016/j.ejpoleco.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Growth, debt burdens and alleviating effects of foreign aid in least developed countries

Abstract: Abstract:In this paper, we explore the potential growth effects of foreign aid when in conjunction with severe debt problems. We first argue that aid, when used to finance debt repayments, does not lead to Dutch Disease while still alleviating an economic problem. A set of empirical estimates show that while inflows of foreign aid in general are not associated with growth in a sample of 38 Least Developed Countries, an interaction term with the level of external debt is significant. We take this as suggestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Likewise, Mallik (2008) took into account 35 years of overseas developmental assistance to six poorest African countries (Central African Republic, Malawi, Niger, Sierra Leone, Mali and Togo) using a cointegration analysis and found the long-term effect of aid on real GDP was negative, for the majority of countries used in the study. Equally, assessing growth and debt burden in least developing countries, Bjerg et al (2011) found that aid has no relationship with growth, but aid is effective in repayment of debt. Barro (1991) and Duc (2006) used a model of growth theory to model overseas developmental assistance for 39 different recipient countries during several time-periods.…”
Section: Cross-country Studiesmentioning
confidence: 99%
“…Likewise, Mallik (2008) took into account 35 years of overseas developmental assistance to six poorest African countries (Central African Republic, Malawi, Niger, Sierra Leone, Mali and Togo) using a cointegration analysis and found the long-term effect of aid on real GDP was negative, for the majority of countries used in the study. Equally, assessing growth and debt burden in least developing countries, Bjerg et al (2011) found that aid has no relationship with growth, but aid is effective in repayment of debt. Barro (1991) and Duc (2006) used a model of growth theory to model overseas developmental assistance for 39 different recipient countries during several time-periods.…”
Section: Cross-country Studiesmentioning
confidence: 99%
“…Sen (2006) and Tarp (2006) stress that aid is beneficial if properly administered. Related research considers the effectiveness of aid to be dependent on the existence of certain features in recipient countries, such as the share of a country's area that lies in the tropics (Daalgard, Hansen, and Tarp 2004), the level of democratization (Svensson 1999), institutional quality (Burnside and Dollar 2004), political stability (Chauvet and Guillaumont 2004), vulnerability to external shocks (Guillaumont and Chauvet 2001), absorptive capacity (Chauvet and Guillaumont 2004), and the level of indebtedness (Bjerg, Bjørnskov, and Holm 2010). However, Easterly, Levine, and Roodman (2004), Rajan and Subramanian (2008), and Doucouliagos and Paldam (2009) show that these results are fragile, being sensitive to small changes in the data set or in the model specification.…”
Section: The Literaturementioning
confidence: 99%
“…Scartascini and Crain (2002) further developed it to apply to multiparty systems, and introduced the term "modified universalism." Given that important variables are seldom provided on an annual basis for the examined period (especially for poor and fragile developing countries), we introduce time periods (following, e.g., Presbitero 2009, andBjerg et al 2011). Within those time periods we calculate the variable averages.…”
Section: Recipient Countries (Dataset D)mentioning
confidence: 99%